Experiences with acidified raw materials and acids in fur animal feed in Finland : formic acid in blue fox feed, long term effects - Koskinen, Nita (dk, 2007)
Fur animal feed production in Finland Annually approximately 400 million kg fur animal feed is manufactured in Finland. The feed is manufactured mainly from domestic feedstuffs. Vitamins and minerals are also added to the feed to meet the requirements of the animals. Fresh feed is composed almost 80 % of meat by-products, fish and cooked or dehydrated barley. In addition, meat and fish meals are also added. Feedstuffs, such as soybean meal or soy concentrate, corngluten and wheatgluten meals, potato protein and are also used when economically viable to do so. Mainly the slaughterhouse by-products and fox carcasses are acidified. Finnish Food Safety Authority controls the use of acids and preservatives. Due to national legislation all slaughter by-products at Finnish slaughterhouses must be acidified to pH 4.0 or below before the by-products may leave the slaughterhouse. According to national legislation slaughter by-products must be grinded to a maximum particle size of 50 mm and the by-products must be treated with either sorbic acid or benzoic acid to prevent outgrowth of yeast and moulds. The most common combination for preservation is formic acid and Na-benzoate. Also sulphuric acid, formic acid- lactic acid solution and sodium metabisulphite solution have been used. Neutralisation is used in Finland. Most common way of neutralisation is the use of soda (Na2CO3). Calcium carbonate (CaCO3) and calcium hydroxide (Ca(OH)2) is also used. Every 15 feed kitchen in Finland take part in a systematic feed quality control by Finnish Fur Breeders Association (FFBA). The quality control requires minimum 2 feed samples per month from each feed kitchen. Feed samples are analysed in an accredited Fur Animal Feed Laboratory (FFBA) and the analysed results are reported monthly to the authorities. The formic acid content (85% HCOOH) is analysed during March - August twice a month.
Keywords: Ko; sinikettu; turkiseläimet; ruokinta; rehut